2021
DOI: 10.1097/ncc.0000000000000923
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexity, Underlying Processes, and Influencing Factors for Optimal Multidisciplinary Teamwork in Hospital-Based Cancer Teams

Abstract: Background Multidisciplinary teamwork has become the standard in care for oncological patients and their treatment trajectory when comprehensive, holistic, and high-quality cancer care is needed. Working together from a variety of perspectives is difficult to achieve and has well-known pitfalls, such as miscommunication and poor coordination. Objective To describe and synthesize the factors influencing and the processes underlying optimal multidisciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 85 publications
5
17
0
Order By: Relevance
“…Overall, we found a coherent pattern, suggesting that policies and guidelines to support MDT functioning sufficiently address the needs and ways of working of all types of MDTMs in Swiss cancer centres. This study is largely replicating a pattern found in MDTMs globally 8 . From a research perspective the tools that this study applied, can be used to carry out comparative analyses between cancer centres in Switzerland and beyond 41 .…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…Overall, we found a coherent pattern, suggesting that policies and guidelines to support MDT functioning sufficiently address the needs and ways of working of all types of MDTMs in Swiss cancer centres. This study is largely replicating a pattern found in MDTMs globally 8 . From a research perspective the tools that this study applied, can be used to carry out comparative analyses between cancer centres in Switzerland and beyond 41 .…”
Section: Resultssupporting
confidence: 59%
“…In the most recent systematic review of team working in cancer teams that we are aware of, Horlait et al 8 reviewed 49 studies carried out across 12 countries. The review offers a framework for considering the evidence base on team working in MDTMs – which includes structural characteristics (of MDTMs, hospitals and healthcare systems), leadership, participation and involvement, and organisational culture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations